Building a credit scoring model to assign a reference score based on credit transaction and relevant profile data - Islam, Saqib Al; Aziz, Rifah Sama; Ahmed, Aritra; Abida, Fauzia (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.